The Jordanian Bank's Compliance Practice on Custom and Letter of Credit - Al-Amaren, Emad Mohammed; Aletein, Sultan Ibrahim (Yustisia, 2022)
The Uniform Custom and Practice (UCP 600), has defined letter of credit as: “Any arrangement, however, named or described, that is irrevocable and thereby constitutes a definite undertaking of the Issuing Bank to honour a complying presentation". UCP 600 is subject to four main principles: Strict Compliance, Autonomy, Documents handling and virtue examination. This study aims to identify the fundamental principles governing letter of credit operation under the Jordanian Banks practice. Through a qualitative and doctrinal legal approach, this study analyses the organization of UCP 600 regarding the principle governing L/C and the extent to which Jordanian banks adhere to the principles of UCP 600. It also examines, via case approach the Jordanian court's approach towards this matter. The findings reveal that the Jordanian banks (Conventional and Islamic) with 100% are fully committed to the UCP. Moreover, this study also has found that Although Jordanian legislators did not regulate letters of credit operations under the commercial law, it can be noticed, based on the commercial law, that the autonomy principle is applicable in Jordan, even if it is applied in a different context.